Effect Inheritance Land Has Not Been Certified Based On Article 96 Of Government Regulation Number 18 Of 2021 - Cecilya Ragnawaty Naibaho; Nia Kurniati; Yusuf Saepul Zamil (PALAR | PAKUAN LAW REVIEW, 2026)
Abstract Inherited land without certification often leads to legal disputes due to weak legal certainty and a high potential for conflict. Article 96 of Government Regulation Number 18 of 2021 requires the use of old evidence, such as girik, petok, or letter C, to be registered no later than February 2, 2026. After this deadline, old evidence will only serve as an administrative reference and will no longer carry full evidentiary force. This research employs a normative juridical method supported by empirical data from the Complete Systematic Land Registration (PTSL) program and is analyzed through the theory of justice and progressive law. The findings indicate that failure to register land results in the loss of formal evidentiary strength and limits heirs in conducting legal acts related to land ownership. Nevertheless, legal protection remains available for heirs acting in good faith, whether through litigation or non-litigation mechanisms, supported by the state's affirmative policies. Thus, the implementation of Article 96 of Government Regulation Number 18 of 2021 should be directed at balancing formal legal certainty with substantive justice, ensuring that the community's land rights are fairly and proportionally protected. Keywords: inherited land, land certificate, Government Regulation Number 18 of 2021, legal certainty, legal protection.